2001
DOI: 10.1287/orsc.12.1.19.10119
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation in the Pharmaceutical Industry: The Use of Organizational Control in Managing Research and Development

Abstract: The literature on the management of R&D professionals strongly advocates managing R&D projects on a project-by-project basis. This literature suggests that projects should be managed differently depending upon project characteristics such as risk, ambiguity, and nonroutineness. While the primary emphasis of the R&D professional literature has been on project teams, the purpose of this study is to examine the impact of organization-wide controls on innovativeness at the firm level. In a sample of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
541
3
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 676 publications
(574 citation statements)
references
References 78 publications
17
541
3
13
Order By: Relevance
“…But in uncertain situations, a procedure cannot be prescribed and administrative and technical barriers may hamper the production process in unexpected situations. Additionally, of particular relevance for innovation companies, several authors warn that too intensive action control may result in routine actions and a resistance to change (Merchant 1985b;Jaworski 1988;Cardinal 2001;Sarin and Mahajan 2001;Bonner 2005). There is consensus that concentration on action control may lead to an overemphasis of internal processes and the inability of employees to deal with uncertainty (Merchant 1985b).…”
Section: H1a: the Extent Of Results Control Is Positively Associated mentioning
confidence: 99%
See 3 more Smart Citations
“…But in uncertain situations, a procedure cannot be prescribed and administrative and technical barriers may hamper the production process in unexpected situations. Additionally, of particular relevance for innovation companies, several authors warn that too intensive action control may result in routine actions and a resistance to change (Merchant 1985b;Jaworski 1988;Cardinal 2001;Sarin and Mahajan 2001;Bonner 2005). There is consensus that concentration on action control may lead to an overemphasis of internal processes and the inability of employees to deal with uncertainty (Merchant 1985b).…”
Section: H1a: the Extent Of Results Control Is Positively Associated mentioning
confidence: 99%
“…It has been confirmed that highly innovative companies train their staff the most (Freel 2005) and personnel control has a positive impact on the likelihood of radical and incremental innovation (Cardinal 2001). Since the importance of personnel control to the generating of innovations seems to be generally accepted, it is hypothesised: …”
Section: H9a: the Extent Of Results Control Is Negatively Associated mentioning
confidence: 99%
See 2 more Smart Citations
“…Organizational structure is regarded as one of the forms of organizational control which aims to encourage organizational members to behave towards organizational goals (Cardinal, 2001). Organizational structure determines how information flows within the organization.…”
Section: Literature Reviewmentioning
confidence: 99%